If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-5+2x=65
We move all terms to the left:
3x-5+2x-(65)=0
We add all the numbers together, and all the variables
5x-70=0
We move all terms containing x to the left, all other terms to the right
5x=70
x=70/5
x=14
| x^2+2x-7=41 | | 5/3x+1/3x=111/3+8/3x | | -6x=186 | | 14/9+1/4t=3 | | 1-2(2x-4)=-(x-12) | | x-(20)=-5 | | 5x+5=98 | | 13/8+1/3t=3 | | x/8+6=-2 | | 14=2(x-7)-x | | 7x-`1=4x+5 | | 2(2t+1)-11=t-(t+8) | | 2(3x+5=6x-4 | | -36+x=-12 | | 3w+4J=39 | | 2/7y+9=-5/7y | | 2x^2-1+64=2x+1 | | -6-7x=-8x-92 | | 6x+3=3(x=9) | | x-9=5+4x | | 10(x-2)(3x+7)=0 | | x+1/3=-21 | | 3x+4(5-5)=7x-20 | | 2x-35=145 | | 9x+5x-4x-5=25 | | 2(9s+11)-10s=2(4s+4)-11 | | 4y-1+y+15=8y+20-6y | | x-9=5+4 | | 6x+35=53 | | A=3.14×r^2 | | 2x3=12 | | 50=36.50+.15m |